Modifications of phraseological units in the light of contemporary French research: An outline of the problem - Krzyżanowska, Anna (Neophilologica, 2019)
Modifications of phraseological units are the effect of deliberate violation by the sender of the established formal and semantic structure of the unit. The transformation operations used in phraseological units have a significant cognitive value, because they show the possibility of transforming units with varying degrees of fixation in the text. Even in the case of a literal understanding of the idiom or its structural decomposition idiomatic meaning remains in the background and it is identified by the recipient thanks to the social stability of the language unit.